CHARACTERISTICS OF FISH PELLETS BASED ON ORGANIC WASTE WITH ANALYSIS OF PHYSICAL AND MECHANICAL PROPERTIES - Sabikah Bassamah; R. Arief Firmansyah; Cahyo Indarto (Universitas Mataram, 2026)
Malang City, as one of the educational centers in East Java, faces challenges in managing organic waste, including within school environments. SMPN 15 Malang produces daily organic waste from its canteen and student activities, such as food scraps, fruit peels, and vegetables, which have not been optimally utilized. Previous studies have shown that organic waste has the potential to be used as an alternative raw material for fish feed, such as pellets derived from biogas sludge. This study aims to engineer school-based organic waste into fish pellets and to analyze their physical, mechanical, and nutritional properties. The materials were tested through a series of analyses including dimensions, expansion ratio, density (true density and single pellet density), porosity, color, Water Absorption Index (WAI), Water Solubility Index (WSI), water stability, and angle of repose. The organic waste was fermented and formulated together with protein-rich ingredients, then processed into pellets in accordance with SNI 9043-4:2025.